The Effects of Various Additive Components on the Sound Absorption Performances of Polyurethane Foams - Shuming Chen; Yang Jiang; Jing Chen; Dengfeng Wang (Advances in Materials Science and Engineering)
Flexible polyurethane (PU) foams comprising various additive components were synthesized to improve their acoustic performances. The purpose of this study was to investigate the effects of various additive components of the PU foams on the resultant sound absorption, which was characterized by the impedance tube technique to obtain the incident sound absorption coefficient and transmission loss. The maximum enhancement in the acoustic properties of the foams was obtained by adding fluorine-dichloroethane (141b) and triethanolamine. The results showed that the acoustic absorption properties of the PU foams were improved by adding 141b and triethanolamine and depended on the amount of the water, 141b, and triethanolamine.